Guidance on the Adaptation for Medium-Sized Enterprises (SMEs) of Transportation Services in Savannakhet Province - BANMANIVONG , Lidsada; VONGKEO, Somphone; XOMVIMANE, Khamphanh; TOUNMANYSONE , Thongsa; INTHAVILAY, Vansisamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This research aimed to explores of the guidance on the adaptation for Medium-Sized Enterprises (SMEs) of transportation services the in Savannakhet Province”. The objective of this study was to examine the overview of Medium-Sized Enterprises (SMEs) of transportation services and study the impacts on Medium-Sized Enterprises (SMEs) of transportation services. Using a data collection as questionnaire with the frequency, percentage of data analysis to demonstrate significance value. In 2019, the research outcomes on study SME transportations overview found that 14 transport companies, 36.84% are exported transport services while 12 transport companies, 31.58% are serviced as the import transportation, the Transport Management System is organized by 12 transport companies, 44.44%, on the other hand 10 transport companies of 37.04% were operated with GPS (Global Positioning System). In a reason of domestic transportation within Savannakhet province to Vientiane capital city be totally 11 companies in 35.48%, the interna-tional transportation and transit cargo depart to Thailand from 14 companies of 51.81% incidentally, 13 transport companies are departed to Vietnam 48.14% as like agricultural commodities 28.95% from 11 transport companies and as alongside construction supply as 23.68% from 9 transport companies. Nonetheless, through studies of SME transportations problem impact found that lack of supportive governance structures, delays in arrival, personnel allocation, and fuel dissipation. While the conducting SME transportation services adaptation guidance is categorized to depend on problem impact as following: the government should support and doing cooperation especially the route facility infrastructure, a good contribute domestic transportation should possess the Collection and Distribution Center, having the transportation timetable in advanced, holding the suitable mode of transportation with features of area within the province and goods, carrying out the personnel management of human resources to schedule employee training and encouragement, decreasing empty shipments are decreasing fuel dissipation making the core computation is for each shipments of mode transportation, vehicles and location scheme.